Plastik Sebagai Bahan Kemasan Makanan - Koentoro Soebijarso; djumarman Djumarman (Jurnal Kimia dan Kemasan, 1979)
The advantage of plastic usage as packaging material are light,not fragile, not rusted, easy colored, easy formed for various designs, available in various types, not expensive, etc.The main factors in selecting of packaging material for food packaging are: the characteristics of the raw material/food material, the characteristics of the packaging material , environmental factors, and the method of food preservation. Physically, plastics for packaging can be divided into rigid plastic, semirigid, and flexible.